2016
DOI: 10.1002/navi.146
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial Scintillation Amplitude Fading Characteristics Across the GPS Frequency Bands

Abstract: Deep signal fading during ionospheric scintillation possesses a threat to GNSS signal tracking and degrades position, navigation, and timing solution accuracy. Understanding the physics and the characteristics of the signal fading is a pre‐requisite to developing robust scintillation mitigation techniques for assured navigation and for utilizing GNSS signals for ionosphere and space weather studies. In this paper, intermediate frequency GPS data collected on Ascension Island in March 2013 are processed to enab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 30 publications
1
40
0
Order By: Relevance
“…A fading model used by the above workers has verified the degraded performance of new L2C and L5 signals with respect to L1 signal. Jiao et al () reported L5 to have smaller tendency toward number of fades compared to L1 and L2C signal during the same period of scintillation and a decreased correlation between the GPS frequencies during strong scintillation. In the present work, effort has been made to compare L1 C/A signal with L2C and L5 signals in terms of loss of lock and cycle slips.…”
Section: Discussionmentioning
confidence: 99%
“…A fading model used by the above workers has verified the degraded performance of new L2C and L5 signals with respect to L1 signal. Jiao et al () reported L5 to have smaller tendency toward number of fades compared to L1 and L2C signal during the same period of scintillation and a decreased correlation between the GPS frequencies during strong scintillation. In the present work, effort has been made to compare L1 C/A signal with L2C and L5 signals in terms of loss of lock and cycle slips.…”
Section: Discussionmentioning
confidence: 99%
“…Strong equatorial scintillation is known to degrade receiver carrier tracking performance, causing measurement error, cycle slips, and even loss of lock signals Seo et al 2009). In the real data analysis presented in our previous publications (Jiao et al 2016;Myer and Morton 2018), cycle slips and loss of lock are frequently observed in commercial receivers in the equatorial region, some of which can last more than 2 h.…”
Section: Introductionmentioning
confidence: 92%
“…In recent years, the availability of massive scintillation measurement data has led to numerous studies focused on the temporal and spectral characteristics of the scintillation signal amplitude and phase (Seo et al 2009(Seo et al , 2011Oliveira et al 2014;Jiao et al 2016). This work will focus on the navigation message bit decoding error (BDE) during strong equatorial scintillation.…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies have provided empirical evidence that the phase scintillation exhibits a high degree of correlation between different GNSS frequencies, including L1, L2 and L5. It has been suggested that this correlation persists except in the case of strong amplitude scintillation, when deep amplitude fades occur (Sokolova et al, 2015;Carrano et al, 2012;Jiao et al, 2016). This implies that even when strong phase scintillation is observed, which is not uncommon at high latitudes, these variations in the carrier will be correlated across frequencies.…”
Section: Ionospheric Scintillationmentioning
confidence: 98%
“…The Cornell Scintillation Model (CSM) (Humphreys et al, , 2010, a popular synthetic signal simulator that generates scintillation amplitude and phase traces, was used to test the AR-based filtering methodology. Recent studies of real equatorial and highlatitude data have shown that scintillation characteristics are frequency-dependent (Carrano et al, 2012;Sokolova et al, 2015;Jiao et al, 2016). While phase disturbances may be correlated, deep amplitude fades tend to occur at different times on different frequencies, thus motivating the potential performance gain of using inter-frequency aiding and multifrequency architectures.…”
Section: Introductionmentioning
confidence: 99%